DEVELOPING CRITICAL THINKING SKILLS THROUGH THE INTERACTIVE METHODS (Konferensiyalar | Conferences, 2024)
The article emphasizes the importance of methodology in teaching, especially in fostering critical thinking skills rooted in scientific perspectives. It explores various ideas and recommendations for improving students' critical thinking abilities, employing specialized techniques and strategies within language learning contexts.